LEARNING WRITING ENGLISH BY ROUND-TABLE STRATEGY; THE EFFECTIVENESS OF STRATEGY - Setyaningrum, Riya Risqi (TELL - US JOURNAL, 2023)
Roundtable strategy is one of the teacher’s efforts in improving the students’ writing English skill. The effectiveness of this strategy has not been proven yet, so this research done to find out the effectiveness of roundtable in learning writing English. The design of research was pre-experimental. The research was done for five meetings to the seventh grade at MTs Nurul Jadid. The data collection were calculated and analyzed by Statistical Product Service Solution (SPSS) 22. The result showed the significance value of pretest was0.074 and post-test was 0.176. The significance value was greater than 0.05, it means the data were normally distributed. The test of hypothesis used paired sample t-test. It showed the sig (2-tailed) value was 0.00. The sig (2-tailed) value was smaller than 0.05. Then Ho was rejected and Ha was accepted. Finally, the effectiveness of roundtable in teaching writing descriptive text showed in hypothesis testing by paired sample t-test and N-Gain score to measure it. N-Gain score was 51%. The conclusion of roundtable strategy was less effective for the seventh grade at MTs. Nurul Jadid Lamongan. The researcher may do collaboration round-table strategy with another strategy to upgrade the students’ writing ability.